Enhancing sustainable solutions for food security in Jordan: using bacterial biofertilizer to promote plant growth and crop yield - Mashatleh, Mohammad; Assayed, Almoayied; Al-Hmoud, Nisreen; Alhaj Ali, Husameddin; Al Abaddi, Rana; Alrwashdeh, Mumen (Frontiers in Sustainable Food Systems, 2024)
Introduction Jordan suffers from agricultural land degradation, water scarcity, increasing in population, and the huge gap between production and consumption. Boosting of food production to meet the demand is one of the solutions. Biofertilizers are substances include beneficial microorganisms (e.g., bacteria) that are important in agricultural soil to improve yield through different mechanisms. The aim of this experiment is to study the impact of using locally produced-microorganisms along with chemical fertilizers to improve the yield of cucumber planting. Methods The experiment was carried out in a greenhouse equipped with all requirements for planting. The planting process of cucumber seedling was implemented using pots filled with soil collected from an agricultural land in the Jordan Valley, and mixed with manure, and categorized in three plots. Mixture of three types of microorganisms (STIMULANT A and B, and PHYTO-EM) along with chemical fertilizers were applied to the soil in some pots. Plants growth and agricultural parameters were observed. Data about crop yield, water consumption, leaf area, and chlorophyll were collected. Lab analysis of soil characteristics was also done to assess the impact of the products on soil. Results The results showed that the yield production was the maximum in the plot of combining the benefits of biological and the chemical fertilizers compared to the control plot by 48%. The same plot showed water saving with 32.4% over the control plot. The bacterial biofertilizers enhanced the seedling growth all the time during the experiment by 14% more than the plants in the control plot. The average leaves area in plot with bio-products was 22.6% bigger than the control plot. In addition, the chlorophyll test indicated that the chlorophyll content was more in plot with biofertilizers. According to the soil analysis, the presence of bacterial biofertilizers enhanced the plant’s absorption of nutrients, and accordingly the EC decreased in the soil. Discussion The results of the experiment showed superiority of plot using the bacterial biofertilizers along with the chemical fertilizer, over the plots either using the chemical fertilizers alone or the bacterial biofertilizers alone. This can be attributed to the addition of bacterial biofertilizers with the chemical fertilizers in appropriate conditions. Our findings highlight the potential for bacterial biofertilizers to significantly improve crop yields and resource efficiency, contributing to food system transformation. This aligns with the UN Sustainable Development Goals, particularly SDG 2 (Zero Hunger) and SDG 15 (Life on Land), by offering sustainable agricultural solutions.